New moon - Meyer, Stephenie (London Atom (Hachette India), 2007)
I stuck my finger under the edge of the paper and jerked it under the tape. 'Shoot,' I muttered when the paper sliced my finger. A single drop of blood oozed from the tiny cut. It all happened very quickly then. 'No!' Edward roared ... Dazed and disorientated, I looked up from the bright red blood pulsing out of my arm - and into the fevered eyes of the six suddenly ravenous vampires.For Bella Swan, there is one thing more important than life itself: Edward Cullen. But being in love with a vampire is more dangerous than Bella ever could have imagined. Edward has already rescued Bella from the clutches of an evil vampire but now, as their daring relationship threatens all that is near and dear to them, they realise their troubles may just be beginning
Keywords: English Fiction; Fiction- Romance & Suspense